2014
DOI: 10.2967/jnumed.114.139782
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic SPECT Measurement of Absolute Myocardial Blood Flow in a Porcine Model

Abstract: Absolute myocardial blood flow (MBF) and myocardial flow reserve (MFR) provide incremental diagnostic and prognostic information over relative perfusion alone. Recent development of dedicated cardiac SPECT cameras with better sensitivity and temporal resolution make dynamic SPECT imaging more practical. In this study, we evaluate the measurement of MBF using a multipinhole dedicated cardiac SPECT camera in a pig model of rest and transient occlusion at stress using 3 common tracers: 201 Tl, 99m Tc-tetrofosmin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 21 publications
2
94
0
14
Order By: Relevance
“…Our results demonstrate that quantification of dynamic SPECT MPI on modern CZT cameras is technically feasible but without specific correction for the different extraction fraction and metabolism of Previous studies exploring quantification of MBF with dynamic planar scintigraphy in humans (18)(19)(20)(21)(22)(23)(24)(25) and with dynamic SPECT in experimental animals (26)(27)(28) have documented the limitations of conventional g-cameras for the dynamic acquisition of datasets required for MBF quantification. The introduction of CZT cameras without the need of detector rotation has allowed proving the concept of dynamic image acquisition for MBF quantification in a recent animal study using microspheres as a standard of reference (6). A recent study has confirmed the feasibility and reproducibility of kinetic analysis of myocardial tracer uptake with a CZT device (29), although no standard of reference for perfusion quantification was available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that quantification of dynamic SPECT MPI on modern CZT cameras is technically feasible but without specific correction for the different extraction fraction and metabolism of Previous studies exploring quantification of MBF with dynamic planar scintigraphy in humans (18)(19)(20)(21)(22)(23)(24)(25) and with dynamic SPECT in experimental animals (26)(27)(28) have documented the limitations of conventional g-cameras for the dynamic acquisition of datasets required for MBF quantification. The introduction of CZT cameras without the need of detector rotation has allowed proving the concept of dynamic image acquisition for MBF quantification in a recent animal study using microspheres as a standard of reference (6). A recent study has confirmed the feasibility and reproducibility of kinetic analysis of myocardial tracer uptake with a CZT device (29), although no standard of reference for perfusion quantification was available.…”
Section: Discussionmentioning
confidence: 99%
“…The recent advances in SPECT technology including semiconductor detector material (cadmium zinc telluride [CZT]) allow acquisition in a nonrotating mode and therefore acquisition of time-activity curves. This may enable absolute MBF and MFR estimation by SPECT as recently shown in experimental animal models (6), which may pave the way for its implementation in clinical routine (7). More knowledge on the impact of the tracer properties on the values obtained from quantification is crucial.…”
mentioning
confidence: 90%
“…26 Wells et al have applied dynamic flow quantification analysis as described by Klein et al to animal images obtained with high-efficiency MPI, demonstrating very good correlations of MBF with invasive microsphere measurements. 27 …”
Section: New Opportunity For High-efficiency Mpimentioning
confidence: 99%
“…Further studies are needed to assess whether availability of transmission to correct for attenuation may enable better modelling of 99m Tc-labelled tracer kinetics. In addition, the new technology with superior sensitivity allows a significant reduction in the administered dose of 99m Tc-labelled tracers [21][22][23], which should also be applied to dynamic SPECT in future studies.With the increasing abundance of dedicated cardiac cameras with solid-state detectors, this technology offers great promise for CFR quantification with dynamic SPECT. However, further studies are needed for validation of this technique with PET measurements in large patient cohorts and with low administered activities, to establish its role in the clinical work-up of patients with known or suspected CAD and to provide data equivalent to the large body of data already accumulated for blood flow quantitation with PET tracers.…”
mentioning
confidence: 99%
“…Further studies are needed to assess whether availability of transmission to correct for attenuation may enable better modelling of 99m Tc-labelled tracer kinetics. In addition, the new technology with superior sensitivity allows a significant reduction in the administered dose of 99m Tc-labelled tracers [21][22][23], which should also be applied to dynamic SPECT in future studies.…”
mentioning
confidence: 99%